Artificial Olfactory Biohybrid System: An Evolving Sense of Smell. Issue 5 (18th December 2022) - Qin, Chuanting; Wang, Yi; Hu, Jiawang; Wang, Ting; Liu, Dong; Dong, Jian; Lu, Yuan
Abstract: The olfactory system can detect and recognize tens of thousands of volatile organic compounds (VOCs) at low concentrations in complex environments. Bioelectronic nose (B‐EN), which mimics olfactory systems, is becoming an emerging sensing technology for identifying VOCs with sensitivity and specificity. B‐ENs integrate electronic sensors with bioreceptors and pattern recognition technologies to enable medical diagnosis, public security, environmental monitoring, and food safety. However, there is currently no commercially available B‐EN on the market. Apart from the high selectivity and sensitivity necessary for volatile organic compound analysis, commercial B‐ENs must overcome issues impacting sensor operation and other problems associated with odor localization. The emergence of nanotechnology has provided a novel research concept for addressing these problems. In this work, the structure and operational mechanisms of biomimetic olfactory systems are discussed, with an emphasis on the development and immobilization of materials. Various biosensor applications and current developments are reviewed. Challenges and opportunities for fulfilling the potential of artificial olfactory biohybrid systems in fundamental and practical research are investigated in greater depth. Abstract : Benefiting from the gradual decipherment of olfaction, artificial olfactory biosensor systems are being developed for applications in industry, security, food, and medicine. Bioinspired receptors and diverse transducers are designed and evolved to improve sensing traces of odorants. Cutting‐edge technologies are integrated to overcome the biosensor challenges of sensitivity, selectivity, reproducibility, stability, and lifetime.